Association of Vitamin E in Pregnancy Induced Hypertension (Medical Forum Monthly, 2024)
Objective: To observe the association of vitamin E with pregnancy induced hypertension.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Gynaecology, Shalamar Hospital, Lahore from July 2016 to December 2016.Methodology: Study was started after ethical approval from institution ethical board and completed within duration of July 2016 to December 2016. SPSS version 23 was used to analyze data. After calculations of frequencies for categorical variables like stratified age, BMI and mean for numerical variables like BMI, vitamin E level. Linear regression was applied to see the association between PIH and vitamin E level. P value ≤0.05 was considered as significant.Results: A total number of 100% (n=323) women were included in this study. The mean age, BMI, parity, gravidity and vitamin E level of the women was 28.64±5.67 years, 28.28±2.81 BMI, 3.03±1.21, 3.71±1.70 and 7.37±2.96(µg/mL)respectively. To check of association of vitamin E level with pregnancy induced hypertension, linear regression was applied and it was observed that BMI and pregnancy with PIH were associated with Vitamin E level with p-values 0.040 and 0.000 respectively.Conclusion: The observations of our study concluded that vitamin E level has significant association with pregnancy induced hypertension in each trimester of pregnancy.